2018
DOI: 10.1111/ecc.12947
|View full text |Cite
|
Sign up to set email alerts
|

Little information about fertility preservation is provided for cancer patients: A survey of oncologists’ knowledge, attitude and current practice

Abstract: The objective of this survey was to explore the knowledge, attitude and current practice of Iranian oncologists about fertility preservation (FP) services provided to cancer patients. Oncologists who completed this survey were a convenience sample of 103 specialists in radiation oncology and haematology who attended large national and international congresses and symposia across Iran. A 23‐item self‐administered questionnaire included questions on knowledge, attitudes and practice. The most well known of the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…In contrast, one study revealed that the likelihood of referring was associated with the gender of the practicing oncologists, with female oncologists more likely to refer [15]. However, a newly published research showed that no statistically significant differences were observed between male and female oncologists regarding the referral behaviors [20]. These differences could be due to the various cultural contexts in which the surveys took place.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, one study revealed that the likelihood of referring was associated with the gender of the practicing oncologists, with female oncologists more likely to refer [15]. However, a newly published research showed that no statistically significant differences were observed between male and female oncologists regarding the referral behaviors [20]. These differences could be due to the various cultural contexts in which the surveys took place.…”
Section: Discussionmentioning
confidence: 93%
“…It is worth noting that the time required for FP is different based on the cancer type and patients' physical condition, so some physicians refuse to discuss the FP issues with the perception that patients could not delay treatment to pursue options when the patients requiring immediate cancer treatment [15,18]. On the contrary, one study showed that some oncologists who believed that discussion should not be held if patients had an exceedingly aggressive form of cancer and required immediate treatment were more likely to discuss FP issues [20]. Thus, it can be seen that preventing a delay in an urgent treatment might not be a barrier for discussing.…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant, especially females did not feel sufficiently informed. An explanation may be that healthcare providers have different knowledge about preservation options for male and female patients (Vesali, Navid, Mohammadi, Karimi, & Omani‐Samani, 2019) and young women tend to receive incomplete information (Wright, Coad, Morgan, Stark, & Cable, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the introduction of guidelines over 15 years ago, studies continue to show that FP services are inadequately provided to adolescent and young adult patients newly diagnosed with cancer. 9,10 This is particularly concerning, given that surveys document that adolescents and young adults prioritize fertility risk conversations and potential pursuit of preservation strategies before initiation of treatment. [11][12][13] Although several studies have shown that establishing structured FP services increases both patient satisfaction and FP utilization rates, their general availability and uptake in pediatric oncology programs are not well defined.…”
Section: Original Contributionsmentioning
confidence: 99%